PENGASINGAN KUASA MENURUT PERSPEKTIF BARAT DAN ISLAM: AMALANNYA DI MALAYSIA: The Separation of Power Between Western and Islamic Perspective: The Application in Malaysia - Che Pa, Bharuddin; Zulkafli, Farizah (Jurnal Syariah, 2014)
The concept of separation of power is a doctrine which recommends separation of powers between the three branches of the government, namely, legislative power, administrative power and judicial power. This article will elaborate on the doctrine of separation of powers according to Western and Islamic perspective as a comparative analysis. This study uses a qualitative approach and comparative method in examining to what extent the application of the concept of separation of power in Malaysia is in line with the principle of Siyasah al-Shar’iyyah. According to the Islamic perspective, power in a country should be based on Islamic law(shari’ah) and the role of Ijtihad of Muslim scholars, while in the Western concept, those in power are free to act according to the decisions made by the existing authority of the country. Malaysia does not practise the absolute concept of separation of powers. Nevertheless, what is practised in Malaysia is the consolidation of power between the legislative and governing bodies, while the judicial branch of power performs independently. This practice does not violate Islamic law principles as long as the Islamic political principles are preserved. However, if there are irregularities by certain parties until there is no justice in society, then that system is not compatible with the Islamic concept.